Population pharmacokinetics of arbekacin in burn patients - Kim, Jong Hyun; Lah, Hyon-oh; Yim, Dong-Seok (European journal of clinical pharmacology, 2008)
The aim of this study was to estimate the pharmacokinetics (PK) of arbekacin in burn patients using a population–PK approach. Therapeutic drug monitoring data consisting of 126 plasma concentrations (including 17 values that were below the quantitation limit) from 47 burn patients were retrospectively analyzed using a mixed effect method ( NONMEM , ver. 6.0). Covariates, such as burn index, age, sex, among others, were tested on the basic one-compartment model. In the basic model, positive correlations of body weight (WT) and creatinine clearance (CLcr) on total clearance (CL) and volume of distributions (V) were assumed. In the final model, V increased with burn index (BI). The final model was: ; . Between-subject variability in terms of CL and V were 35 and 39%, respectively. The CL of our burn patients was significantly greater than that reported in unburned patients, and V increased proportionally with increasing BI.